Conducting computer security assessments at nuclear facilities. (International Atomic Energy Agency, 2016)
"Computer security is increasingly recognized as a key component in nuclear security. As technology advances, it is anticipated that computer and computing systems will be used to an even greater degree in all aspects of plant operations including safety and security systems. A rigorous and comprehensive assessment process can assist in strengthening the effectiveness of the computer security programme. This publication outlines a methodology for conducting computer security assessments at nuclear facilities. The methodology can likewise be easily adapted to provide assessments at facilities with other radioactive materials."--Publisher's description.